To solve the equation \( 2 \cdot (x - 3) = 0 \) using the Zero Product Property, we first set the equation equal to zero. Since \( 2 \) is a non-zero constant, we can find the solution by focusing on the factor \( (x - 3) \).
According to the Zero Product Property, if the product of two factors is zero, at least one of the factors must be zero. Therefore, we can set the factor equal to zero:
\[ x - 3 = 0 \]
Now, we can solve for \( x \):
\[ x = 3 \]
Thus, the value that makes the statement true is \( x = 3 \).
So, the final answer is: The value that makes the statement true is \( x = \mathbf{3} \).